Demographic factors as correlate of perceived job performance of university libraries’ personnel in southwest, Nigeria - Adekunle, Fisayo Adesola; Ikegune, Daniel Olusegun (Communicate: Journal of Library and Information Science, 2025)
This study investigated demographic factors as correlate of perceived job performance of university libraries’ personnel in Southwest, Nigeria. The survey design of the correlational type was adopted for this study. The population of the study consists 219 university libraries’ personnel in Southwest, Nigeria. While, the purposive sampling technique was used to select the sample for the study. A total of 219 questionnaires were distributed across the universities with a retrieval success of 187 copies, representing 85.4% return rate. Data were analysed using percentages and Pearson Product Moment Correlation analysis. The findings of this study revealed that the level of perceived job performance of university libraries’ personnel in Southwest, Nigeria is high (mean=98.26). Findings also showed a correlation between perceived job performance of university libraries’ personnel and age (r = .141*, P <.05), and gender (r = .175*, P <.05), and academic qualification (r = .322**, P <.05), and designation (r = .113**, P <.05), and years of work experience (r = .244**, P <.05) respectively. Therefore, the null hypothesis is rejected. That is, there is a significant relationship between the demographic factors (age, gender, academic qualification, designation and years of experience) of university libraries’ personnel and their perceived job performance. It was recommended that libraries’ personnel should always ensure they work on their demographic factors and develop themselves technically and professionally by acquiring more skills that will enable them to be more productive such that will improve high perceived job performance.